High‐protein diet more effectively reduces hepatic fat than low‐protein diet despite lower autophagy and FGF21 levels. (21st July 2020) - Xu, Chenchen; Markova, Mariya; Seebeck, Nicole; Loft, Anne; Hornemann, Silke; Gantert, Thomas; Kabisch, Stefan; Herz, Kathleen; Loske, Jennifer; Ost, Mario; Coleman, Verena; Klauschen, Frederick; et al.
Abstract: Background and aims: Non‐alcoholic fatty liver disease (NAFLD) is becoming increasingly prevalent and nutrition intervention remains the most important therapeutic approach for NAFLD. Our aim was to investigate whether low‐ (LP) or high‐protein (HP) diets are more effective in reducing liver fat and reversing NAFLD and which mechanisms are involved. Methods: 19 participants with morbid obesity undergoing bariatric surgery were randomized into two hypocaloric (1500‐1600 kcal/day) diet groups, a low protein (10E% protein) and a high protein (30E% protein), for three weeks prior to surgery. Intrahepatic lipid levels (IHL) and serum fibroblast growth factor 21 (FGF21) were measured before and after the dietary intervention. Autophagy flux, histology, mitochondrial activity and gene expression analyses were performed in liver samples collected during surgery. Results: IHL levels decreased by 42.6% in the HP group, but were not significantly changed in the LP group despite similar weight loss. Hepatic autophagy flux and serum FGF21 increased by 66.7% and 42.2%, respectively, after 3 weeks in the LP group only. Expression levels of fat uptake and lipid biosynthesis genes were lower in the HP group compared with those in the LP group. RNA‐seq analysis revealed lower activity of inflammatory pathways upon HP diet. Hepatic mitochondrial activity and expression of β‐oxidation genes did not increase in the HP group. Conclusions: HP diet more effectively reduces hepatic fat than LP diet despite of lower autophagy and FGF21. Our data suggest that liver fat reduction upon HP diets result primarily from suppression of fat uptake and lipid biosynthesis.